2016
DOI: 10.1111/liv.13058
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of magnetic resonance imaging to transient elastography and serum markers for liver fibrosis detection

Abstract: Background & Aims Establishing accurate non-invasive methods of liver fibrosis quantification remains a major unmet need. Here, we assessed the diagnostic value of a multiparametric magnetic resonance imaging (MRI) protocol including diffusion-weighted imaging (DWI), dynamic contrast-enhanced (DCE)-MRI and magnetic resonance elastography (MRE) in comparison with transient elastography (TE) and blood tests [including ELF (Enhanced Liver Fibrosis) and APRI] for liver fibrosis detection. Methods In this single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 42 publications
8
59
0
Order By: Relevance
“…One study showed a positive predictive value, negative predictive value, and overall accuracy of 100%, 99.9% and 96.4%, for diagnosing cirrhosis compared with controls [116]. DWI does not perform as well as MR elastography [117,99,118]. In comparative study, MR elastography demonstrated higher sensitivity and specificity in predicting fibrosis scores ≥F2 (91% and 97%), ≥F3 (92% and 95%), and F4 (95% and 87%) compared with DWI (84% and 82%, 88% and 76%, and 85% and 68%, respectively) [118].…”
Section: Diffusion Weighted Imaging (Dwi)mentioning
confidence: 99%
See 2 more Smart Citations
“…One study showed a positive predictive value, negative predictive value, and overall accuracy of 100%, 99.9% and 96.4%, for diagnosing cirrhosis compared with controls [116]. DWI does not perform as well as MR elastography [117,99,118]. In comparative study, MR elastography demonstrated higher sensitivity and specificity in predicting fibrosis scores ≥F2 (91% and 97%), ≥F3 (92% and 95%), and F4 (95% and 87%) compared with DWI (84% and 82%, 88% and 76%, and 85% and 68%, respectively) [118].…”
Section: Diffusion Weighted Imaging (Dwi)mentioning
confidence: 99%
“…Similarly, a meta-analysis showed DWI distinguishing F0–F1 from F2–F4 with a sensitivity of 77%, specificity of 78%, and AUC of 0.83; less reliable than MR elastography [99]. A more recent study showed that for detection of advanced fibrosis (F3–F4), AUCs were 0.94 for MR elastography and 0.79 for DWI [117]. …”
Section: Diffusion Weighted Imaging (Dwi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Liver stiffness measurement can also be used to detect and assess severity of portal hypertension (2, 3), in addition to spleen stiffness (4). Multiple studies showed high accuracy of MRE for liver fibrosis detection and stratification with equivalent to higher performance than other noninvasive modalities, including transient elastography and serum markers (58). Moreover, MRE provides larger sampling compared to ultrasound (US) elastography techniques with high repeatability of LS measurements (9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…2 The advantages of MRI are the whole liver coverage, with large sampling and lack of ionizing radiation, and high sensitivity for HCC detection. Despite these promising results, only a few studies have compared the diagnostic performance of mpMRI for liver fibrosis staging, showing greater performance of MRE against morphologic criteria 4,5 and DCE-MRI and DWI, 6,7 with improved detection of liver fibrosis and cirrhosis when using a multiparametric approach. 3 Among these, measurement of liver stiffness with MRE has gained clinical acceptance, as it is a highly accurate method for assessing liver fibrosis.…”
mentioning
confidence: 99%